Hydrogen-peroxide intercalated expanded graphite facilitates large enhancement in thermal conductivity of polyetherimide/graphite nanocomposites - Fatema Tarannum; Swapneel Danayat; Avinash Nayal; Zarin Tasnim Mona; Roshan Sameer Annam; Keisha B. Walters; Jivtesh Garg (Journal of Materials Research and Technology)
In this work, we prepared expanded graphite (EG) filler using hydrogen peroxide (H2O2) as an oxidizing agent to study its impact on the thermal conductivity (k) of polyetherimide (PEI) composite, compared to EG prepared using sodium chlorate (NaClO3). Sulfuric acid was used as the primary intercalating agent for both synthesis routes. The use of H2O2 prepared EG (EG-H2O2) led to a remarkable ∼4030% enhancement (9.5 Wm−1K−1) in k of the PEI/EG composite, while the use of NaClO3 prepared EG (EG-NaClO3) led to a much smaller enhancement of ∼2190% (5.3 Wm−1K−1), at 10 wt% EG composition compared to kPEI (∼0.23 Wm−1K−1). Such findings exceed the current state-of-art in EG-based polymer composites. Detailed characterization was performed to understand the properties of EG-H2O2 and EG-NaClO3. Raman analysis revealed that H2O2 resulted in relatively defect-free EG (ID/IG ratio ∼0.04), thus preserving the k of graphite (∼2000 Wm−1K−1). Use of NaClO3, however, led to a large defect density (ID/IG ratio ∼0.25), yielding graphite with significantly diminished k. Furthermore, through-plane thermal diffusivity of EG-H2O2 paper was measured to be 9.5 mm2s-1 while that of NaClO3 case was measured to be 6.7 mm2s-1, thus directly confirming the beneficial impact of H2O2 in preserving the high k of graphene. X-ray photoelectron spectroscopy (XPS) revealed that the higher number of defects in EG-NaClO3 are due to the higher degree of oxidation induced by NaClO3. The results demonstrate the potential of EG-H₂O₂ as an efficient filler for achieving high thermal conductivity polymer composites.